Strategi Optimalisasi Dana Desa dalam Pemberdayaan Ekonomi melalui Pengembangan Wisata - Saifuddin; Ahmad Mustofa (JURNAL ILMIAH EDUNOMIKA, 2025)
Development of the village tourism sector is one of the effective strategies in improving the economy of the community at the local level. Optimal utilization of Village Funds can encourage community economic empowerment through the development of tourism potential owned by the village. The purpose of this study is to analyze how village funds can be optimally utilized to support economic empowerment based on tourism development. This involves understanding local tourism potential and how it can improve the economic conditions of the community. This study uses a descriptive qualitative approach, examining village fund management practices that are oriented towards tourism development and community empowerment. This method allows for a comprehensive understanding of its effectiveness. The results of the discussion show that effective strategies include participatory planning, strengthening human resource capacity, developing local MSMEs, strengthening village institutions such as BUMDes, and transparency and accountability in fund management. Tourism development that is carried out in a targeted and sustainable manner can create new jobs, increase community income, and strengthen local cultural identity. Keywords: Village Funds, economic empowerment, village tourism, development strategies, village communities